2016
DOI: 10.1136/annrheumdis-2016-209300
|View full text |Cite
|
Sign up to set email alerts
|

Do high numbers of salivary gland-infiltrating B cells predict better or worse outcomes after rituximab in patients with primary Sjögren's syndrome?

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
1
16
3
Order By: Relevance
“…Explanations for the apparent discrepancy between the study of Cornec et al and our study have been extensively discussed elsewhere [60,61]. Our findings that high absolute numbers and proportions of B cells in the parotid gland are associated with ESSDAI response suggest that the number of B cells in the target tissue influences systemic disease activity.…”
Section: Predictors Of Response To Rituximabcontrasting
confidence: 57%
“…Explanations for the apparent discrepancy between the study of Cornec et al and our study have been extensively discussed elsewhere [60,61]. Our findings that high absolute numbers and proportions of B cells in the parotid gland are associated with ESSDAI response suggest that the number of B cells in the target tissue influences systemic disease activity.…”
Section: Predictors Of Response To Rituximabcontrasting
confidence: 57%
“…In essence, we showed in our paper that absolute numbers of CD20+ cells/mm 2 of parenchyma of parotid gland tissue are predictive for the responsiveness of patients with pSS to rituximab (RTX) treatment. Cornec et al argue that there is a discrepancy in outcomes presented in their study and our study,1 as they observed that a high proportion of minor salivary gland B cells predict the absence of a clinical response to RTX 3. As we will show and explain here, there is no inconsistency between the two studies and most of the apparent discrepancy is likely the result of differences in how the tissues are analysed and how the disease activity is established.…”
contrasting
confidence: 59%
“…With great interest we have read the letter to the editor by Cornec et al 1 regarding our paper ‘Towards personalised treatment in primary Sjögren's syndrome (pSS): baseline parotid histopathology predicts responsiveness to rituximab treatment’ 2. In essence, we showed in our paper that absolute numbers of CD20+ cells/mm 2 of parenchyma of parotid gland tissue are predictive for the responsiveness of patients with pSS to rituximab (RTX) treatment.…”
mentioning
confidence: 75%
See 2 more Smart Citations